AKMB-news : Informationen zu Kunst, Museum und Bibliothek. (Düsseldorf : Arbeitsgemeinschaft der Kunst- und Museumsbibliotheken (AKMB), 1995)
The Arbeitsgemeinschaft der Kunst- und Museumsbibliotheken (AKMB) was founded in 1995 as an association to represent the interests and provide advice to art and museum libraries in the German-speaking world, which are generally small and have few members of staff. The aim of the AKMB is to improve the performance of art and museum libraries and documentation centres through increased cooperation. The working group now has circa 260 institutional and personal members.(www.arthistoricum.net)
Https://www.arthistoricum.net/netzwerke/akmb
Online: https://journals.ub.uni-heidelberg.de/index.php/akmb-news
Duits
Tijdschriften
Keywords: museumbibliotheken; kunstbibliotheken